Prediagnosis ultra-processed food consumption and prognosis of patients with colorectal, lung, prostate, or breast cancer: a large prospective multicenter study - Pu, Jian-Yuan; Xu, Wei; Zhu, Qian; Sun, Wei-Ping; Hu, Jie-Jun; Cai, Dong; Zhang, Jun-Yong; Gong, Jian-Ping; Xiong, Bin; Zhong, Guo-Chao (Frontiers in Nutrition, 2023)
Background and Aims: Whether ultra-processed food consumption is associated with cancer prognosis remains unknown. We aimed to test whether prediagnosis ultra-processed food consumption is positively associated with all-cause and cancer-specific mortality in patients with colorectal, lung, prostate, or breast cancer.Methods: This study included 1100 colorectal cancer patients, 1750 lung cancer patients, 4336 prostate cancer patients, and 2443 breast cancer patients. Ultra-processed foods were assessed using the NOVA classification before the diagnosis of the first cancer. Multivariable Cox regression was used to calculate hazard ratio (HR) and 95% confidence interval (CI) for all-cause and cancer-specific mortality.Results: High ultra-processed food consumption before cancer diagnosis was significantly associated with an increased risk of all-cause mortality in lung (HRquartile 4 versus 1: 1.18; 95% CI: 0.98, 1.40; Ptrend=0.021) and prostate (HRquartile 4 versus 1: 1.18; 95% CI: 1.00, 1.39; Ptrend=0.017) cancer patients in a nonlinear dose-response manner (all Pnonlinearity<0.05), whereas no significant results were found for other associations of interest. Subgroup analyses additionally revealed a significantly positive association with colorectal cancer-specific mortality among colorectal cancer patients in stages Ⅰ and Ⅱ but not among those in stages Ⅲ and Ⅳ (Pinteraction=0.006), and with prostate cancer-specific mortality among prostate cancer patients with body mass index <25 but not among those with body mass index ≥25 (Pinteraction=0.001).Our study suggests that reducing ultra-processed food consumption before cancer diagnosis may improve the overall survival of patients with lung or prostate cancer, and the cancerspecific survival of certain subgroups of patients with colorectal or prostate cancer.